Inference Instruction to Support Reading Comprehension for Elementary Students With Learning Disabilities. (May 2017) - Hall, Colby; Barnes, Marcia A.
Making inferences during reading is a critical standards-based skill and is important for reading comprehension. This article supports the improvement of reading comprehension for students with learning disabilities (LD) in upper elementary grades by reviewing what is currently known about inference instruction for students with LD and providing detailed suggestions and a five-step process for teaching students to make text-connecting and knowledge-based inferences while reading. By bolstering this key reading comprehension skill in the upper elementary grades, teachers can better prepare students for the increased reading comprehension demands of middle school.